2018
DOI: 10.1159/000490772
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Kidney-Protective Effects of the Human Chorionic Gonadotropin Derivate EA-230

Abstract: The systemic inflammatory response following infectious or non-infectious insults is related to morbidity (including acute kidney injury) and mortality. Pregnancy is associated with immunotolerance and an increased glomerular filtration rate. EA-230, a linear tetrapeptide (Alanine-Glutamine-Glycine-Valine), derived from the β-chain of the human chorionic gonadotropin hormone, has shown immunomodulatory and renoprotective properties in several pre-clinical animal models of systemic inflammation. Furthermore, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the latter, surgical damage and stress result in the release of a multitude of danger-associated molecular patterns, ischemia-reperfusion injury, hemorrhagic shock, and possibly translocation of (components of) microorganisms from the gut to the circulation ( 3 , 17 19 ). Nevertheless, previous animal studies have demonstrated immunomodulatory effects of EA-230 in various types of inflammation, including models of ischemia-reperfusion injury ( 34 36 ), and hemorrhagic shock ( 31 ). These models recapitulate distinct aspects of the inflammatory response observed following cardiac surgery and therefore may render this explanation for the absence of immunomodulatory effects in the current study less plausible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter, surgical damage and stress result in the release of a multitude of danger-associated molecular patterns, ischemia-reperfusion injury, hemorrhagic shock, and possibly translocation of (components of) microorganisms from the gut to the circulation ( 3 , 17 19 ). Nevertheless, previous animal studies have demonstrated immunomodulatory effects of EA-230 in various types of inflammation, including models of ischemia-reperfusion injury ( 34 36 ), and hemorrhagic shock ( 31 ). These models recapitulate distinct aspects of the inflammatory response observed following cardiac surgery and therefore may render this explanation for the absence of immunomodulatory effects in the current study less plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with EA-230 attenuated pro-inflammatory cytokine release, prevented organ dysfunction and renal injury, and improved survival in several animal models of systemic inflammation (27)(28)(29)(30)(31)(32)(33). Furthermore, EA-230 mitigated renal injury and improved survival in murine models of renal transplantation and renal ischemia-reperfusion injury (34)(35)(36). Finally, EA-230 was shown to be well tolerated in phase 1 studies (37) and attenuated the release of inflammatory mediators during experimental human endotoxemia (38).…”
mentioning
confidence: 99%
“…The latter has been pursued by several companies. The AMPs OP-145 ( Nell et al, 2006 ), P113 ( Woong et al, 2008 ), LTX-109 ( Midura-Nowaczek and Markowska, 2014 ), and EA-230 ( Van Groenendael et al, 2018 ) all consist of a lower number of amino acids as compared to their “original” peptide LL-37, histatin-5, bovine lactoferrin and loop-2 of β-hCG, respectively. Beside truncation of AMPs, the synthesis of ultra-short AMPs such as the 5-amino acid linear peptide SGX942 further reduces the production costs of AMPs ( Kudrimoti et al, 2016 ).…”
Section: Improvement Strategiesmentioning
confidence: 99%